Community-Based Workforce for COVID-19 Contact Tracing and Prevention Activities in New York City, July–December 2020. (November 2022) - Udeagu, Chi-Chi N.; Huang, Jamie; Misra, Kavita; Terilli, Thomas; Ramos, Yasmin; Alexander, Martha; Kim, Christine; Madad, Syra; Williams, Reba; Bethala, Samira; Pitiranggon, Masha; Blaney, Kathleen; et al.
Objectives: High rates of hospitalization and death disproportionately affected Black, Latino, and Asian residents of New York City at the beginning of the COVID-19 pandemic. To suppress COVID-19 transmission, New York City implemented a workforce of community engagement specialists (CESs) to conduct home-based contact tracing when telephone numbers were lacking or telephone-based efforts were unsuccessful and to disseminate COVID-19 information and sanitary supplies. Materials and Methods: We describe the recruitment, training, and deployment of a multilingual CES workforce with diverse sociodemographic backgrounds during July–December 2020 in New York City. We developed standard operating procedures for infection control and safety measures, procured supplies and means of transportation, and developed protocols and algorithms to efficiently distribute workload. Results: From July through December 2020, 519 CESs were trained to conduct in-person contact tracing and activities in community settings, including homes, schools, and businesses, where they disseminated educational materials, face masks, hand sanitizer, and home-based specimen collection kits. During the study period, 94 704 records of people with COVID-19 and 61 246 contacts not reached by telephone-based contact tracers were referred to CESs. CESs attempted home visits or telephone calls with 84 230 people with COVID-19 and 49 303 contacts, reaching approximately 55 592 (66%) and 35 005 (71%), respectively. Other CES activities included monitoring recently arrived travelers under quarantine, eliciting contacts at point-of-care testing sites, and advising schools on school-based COVID-19 mitigation strategies. Practice Implications: This diverse CES workforce allowed for safe, in-person implementation of contact tracing and other prevention services for individuals and communities impacted by COVID-19. This approach prioritized equitable delivery of community-based support services and resources.